Screening des pesticides dans les céréales par GC-MS - SIAH , Manar; OUARET MALAK , Nermine Hibat Ellah; DJELLABI , Roumaissa Nour EL Imane; DEHEMCHI , Rania; BOUCHALA , Faiza (Encadrant) (Université Sétif1 Ferhat Abbas. Faculté de Médecine., 2024)
ticides are chemical substances used to protect crops from pests, diseases, and weeds. Their use is widespread in modern agriculture to maximize yields and ensure food security. However, there are growing concerns about their impact on the environment and human health. This thesis is part of this objective by proposing the development and analytical validation of a method for screening certain pesticides in cereals, in particular wheat and dried vegetables by GC-MS. The research of multi-residues concerned Chlorpyrifos, Thiamethoxam, Alpha benzoepine, Kresoxim methyl, Endrin, Tebuconazol, Epoxiconazol, Bifenthrin, Lambda cyhalothrin, Cyfluthrin, Deltamethrin, Cypermethrin which were analyzed by different techniques in order to optimize the method. The approach of this work will include several key steps: the selection of pesticides to be analyzed, the optimization of chromatographic and spectrometric conditions, the development of sample extraction and purification protocols, and finally, the validation of the method according to the criteria of accuracy, precision, linearity, limit of detection (LOD) and limit of quantification (LOQ). Pesticide residue analysis by gas chromatography-mass spectrometry (GC-MS) remains an essential and effective method for ensuring food and environmental safety. Thanks to its sensitivity and ability to identify a wide range of compounds. This study highlights the need to improve pesticide management practices and quality controls to ensure the food safety of cereals marketed in Algeria.
Keywords: pesticides; céréales; GC-MS; multi résidus; LD; LQ